Pengembangan E-LKPD (Lembar Kerja Elektronik) Sains Berdasarkan Model Pembelajaran "RADEC" untuk Meningkatkan Kemampuan Berpikir Kritis Siswa di Sekolah Indonesia di Kuala Lumpur - Hanif Krisna Adhiansyah; Mashudi Mashudi; Sri Wahyuni (JPPS (Jurnal Penelitian Pendidikan Sains), 2026)
Objective:  The Indonesian School of Kuala Lumpur is an educational institution established by the Indonesian Ministry of Education to facilitate learning for Indonesian students in Malaysia. This study aims to develop an electronic student worksheet (E-LKPD) to enhance students’ critical thinking skills at the Indonesian School of Kuala Lumpur. The study adopts the RADEC learning model, as it is considered capable of fostering optimal collaboration aligned with 21st-century learning competencies. Method: This study employs a Research and Development (R&D) approach using the ADDIE development model. Data on validity were obtained from three validators using validation sheets. Practicality was assessed by three observers using observation sheets. Effectiveness was evaluated using the SPSS One-Group Posttest-Only design and supported by student response questionnaires. Data analysis for validity and practicality was conducted based on the average scores provided by validators and observers. The effectiveness analysis involved normality testing and one-sample tests. Results: The findings indicate an improvement in students’ critical thinking skills, as demonstrated by the results of the one-sample test. This suggests that the E-LKPD based on the RADEC learning model is effective in enhancing critical thinking skills, particularly in science learning on the topic of vibrations and waves. Therefore, the developed teaching materials are recommended for use in science instruction, especially to improve students’ critical thinking skills. Novelty: This study offers an innovation in instructional media through the development of E-LKPD integrated with the RADEC learning model to enhance the critical thinking skills of Indonesian students in Kuala Lumpur.